Study of Provenance and Site Variability on Calorific Value and Other Fuel Properties of Teak Stem - Asri Prasaningtyas; Joko Sulistyo (Wood Research Journal, 2014)
Currently  Perum Perhutani has  conducted  efforts  to  improve  the   productivity  of  teak  forest  by   provenance  trial. However, only a few  studies have so  far considered the  variation of these main  fuel  properties of wood under the  influence of external factors such as location and provenance. On the  other side, the  huge amount of waste was regularly generated from primary  and secondary  wood processings.  Therefore, in  this  research, the  calorific  value  and other fuel  properties  were investigated and related to provenance and growth site. This research used the  stem wood and bark of five provenances (1 to 5) of teaks that  were planted at  three sites  of Perhutani stand (Bojonegoro, Ngawi, Ciamis). The fuel  characterisctics of bark were only evaluated  at  Ciamis  site.  Compared  to  bark, wood generally had lower values  in  ash content, volatile  matter content, and density,  but  had higher values in fixed  carbon content, calorific  value, and Fuelwood Value Index levels. The caloric  values of  teak  wood and  bark were 4,191~4,520 cal/g  and 3,545~3,939 cal/g,  respectively.  Provenance and site interaction had significant effect to the ash content, density, and calorific value in wood. The samples from  Ciamis site (code Ft) had the  highest level  in  calorific  value. However, the  relation  between calorific  value and density  is  not  clear in  this experiment. With regard to bark, provenance 3 (Ft) showed the  best energy properties.